Sonata for Violin and Piano in A minor, Simrock edition - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Bonn; N. Simrock; Germany, 2023)
Early edition of the parts of the Sonata for violin and piano in A minor, op. 23, separate edition published by Simrock in 1802 or 1803.